Reducing enteric methane emission in dairy goats: impact of dietary inclusions of quebracho tannin extract on ruminal microbiota - Cremonesi, Paola; Severgnini, Marco; Battelli, Marco; Monistero, Valentina; Penati, Martina; Gazzonis, Alessia Libera; Castiglioni, Bianca; Rapetti, Luca; Manfredi, Maria Teresa; Addis, Maria Filippa (Frontiers in Microbiology, 2025)
IntroductionCondensed tannins (CT) influence ruminal microbiota, feed digestibility, and methane emissions, yet their effects in goats are poorly understood.MethodsThis study evaluated the impact of dietary quebracho CT extract at 0%, 2%, 4%, or 6% of dry matter on the composition of the dairy goat ruminal microbiota with a two-times repeated 4 × 4 Latin square design. Bacterial, archaeal, fungal, and protozoan communities were analyzed at the end of each feeding period for relative abundance changes, and their relationship to methane production, nutrient digestibility and feed efficiency were also assessed.ResultsIncreasing CT levels reduced alpha- and beta-diversity, with the 6% CT diet showing the most pronounced decline. CT inclusion induced phylum-level shifts in fiber-degrading microbes, including inversion of the Firmicutes to Bacteroidota ratio. Prevotellaceae and Succiniclasticum, tolerant to CT, increased significantly (P < 0.05), in line with higher propionate and lower methane production. The proteolytic bacteria Anaerolineaceae and Synergistaceae decreased (P < 0.05), consistently with the reduced isobutyrate and isovalerate ruminal concentration and with the reduced urinary nitrogen excretion. Methanobrevibacter, a key methane producer, was reduced by dietary CT (P < 0.05). The overall fungal biodiversity was also significantly changed (P < 0.05); the fiber-degrading Liebetanzomyces decreased, while the tannin-degrading Aspergillus increased (P < 0.05). Concerning protozoa, Diplodinium was reduced (P < 0.05) and Polyplastron and Isotrichia were increased (P < 0.05) by dietary CT.DiscussionThese and other microbial abundance changes correlated with reduced methane emission, altered fiber and protein digestibility, and modified volatile fatty acid (VFA) profiles. This study shows that decreased nutrient degradability in the rumen due to higher dietary CT alters the goat rumen microbiota and clarifies microbial taxa changes in relation to the zootechnical outcomes, including reduced methane production.